1998
DOI: 10.1038/566
|View full text |Cite
|
Sign up to set email alerts
|

The chromo and SET domains of the Clr4 protein are essential for silencing in fission yeast

Abstract: Heritable inactivation of specific regions of the genome is a widespread, possibly universal phenomenon for gene regulation in eukaryotes. Self-perpetuating, clonally inherited chromatin structure has been proposed as the explanation for such phenomena as position-effect variegation (PEV) and control of segment determination and differentiation in flies, X-chromosome inactivation and parental imprinting in mammals, gene silencing by paramutation in maize and silencing of the mating-type loci in yeasts. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
121
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 27 publications
4
121
1
Order By: Relevance
“…Previous studies have demonstrated that chromo domain-containing proteins, including Su(var)3-9 and its orthologs, localize to regions of chromatin that are transcriptionally silenced (1,22,39). Our own subnuclear localization of SUV39H1 to electron-dense nuclear foci supports the notion that SUV39H1 may associate with transcriptionally inactive chromatin.…”
Section: Sbf1 Physically Associates With the Set Domain Of Suv39h1supporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies have demonstrated that chromo domain-containing proteins, including Su(var)3-9 and its orthologs, localize to regions of chromatin that are transcriptionally silenced (1,22,39). Our own subnuclear localization of SUV39H1 to electron-dense nuclear foci supports the notion that SUV39H1 may associate with transcriptionally inactive chromatin.…”
Section: Sbf1 Physically Associates With the Set Domain Of Suv39h1supporting
confidence: 86%
“…The functions of such domains have been implicated in the epigenetic control of developmental gene expression in Drosophila (38), proper sister chromatid segregation during meiosis (11), and telomeric and centromeric silencing in yeast (22,35). The molecular mechanisms that regulate these and other properties of higher-order chromatin are essentially unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning Suv(ar)3-9, inactivation of its homologue Clr4 by mutation in the yeast Schizosaccharomyces pombe relieves heterochromatin silencing at centromeres (Ivanova et al, 1998). Since HP1 is known to interact with Suv(ar)3-9 (Aagaard et al, 1999), it is reasonable to suppose that HP1 might be involved in the silencing function of Suv(ar)3-9.…”
Section: Spatio-temporal Chromatin Organization and Regulation Of Genmentioning
confidence: 99%
“…Heterochromatin proteins, in particular Swi6/HP1, aid in donor choice (5,9). Factors that affect Swi6 localization at the mat locus impair mating-type switching (17)(18)(19)(20)(21). Swi6 facilitates cell-type-specific spreading of a recombination-promoting complex (RPC) (18).…”
mentioning
confidence: 99%